A South–North research agenda for cryotourism in a warming world - Bachmann-Vargas, Pamela; Demiroglu, O. Cenk; Ruiz Pereira, Sebastián; Bohn, Dorothee; Vereda, Marisol; Gale, Trace; Barrena, José (Frontiers in Human Dynamics, 2025)
Cryotourism is a distinct form of tourism which is based on ice and snow cover and is thus highly determined by climatic conditions. While a considerable body of literature addresses the tourism-climate change nexus in (sub-)Arctic and European Alpine regions, little is known about the situation in South American high mountain and sub-Antarctic areas. Against this background, this perspective article presents a research agenda for cryotourism-climate change nexus from a South–North perspective. The initial step toward this objective was an 18-days research visit in Chile and Argentina during January and February 2024. Drawing upon our field notes, current literature and the latest developments in ice and snow-based tourism, we propose three key dimensions for a research agenda, namely: (a) tourism mobilities and southward spatial substitution, (b) socio-ecological implications of cryotourism for local communities, and (c) governance challenges for tourism stakeholders and policymakers. We contend that interdisciplinary and transdisciplinary approaches to tourism and climate change research are key aspects to account for the global nature of tourism mobility flows, and the interlinks between local and global processes and impacts of climatic environmental transformations.